EVALUASI KESESUAIAN DAN KEMAMPUAN LAHAN TERHADAP RTRW KABUPATEN KOTABARU, KALIMANTAN SELATAN - I Made Haribhawana Wijaya; Lilik Budi Prasetyo; Omo Rusdiana (Graduate School Bogor Agricultural University (SPs IPB), 2015)
Spatial planning is prepared to maintain and support the improvement of environment consider to the limited capacity of the environment and its natural resources. The land use which is uncompatible with the Regional Land Use Plan (RTRW) and tend to support economic growth by relying on its natural resources without putting any efforts to increase their environmental values can cause all living organism in danger. One of the environmental issue is spatial problem at District of Kotabaru. This study aimed to evaluate Kotabaru’s spatial plans (RTRW) based on suitability of forest functions, land capability, and landcover. The method used in this study is Geographic Information System (GIS) based for spatial analysis: suitability of forest functions, land capability and identification of land cover. The result showed that there are some inconsistencies against the RTRW of Kotabaru, such as 1). The suitability of forest functions is about 188073,11 Ha (27,66% area of study). The region inconsistency happened mostly in karst area toward annual plantation area; 2) Land capability is about 62967,02 Ha (9,28% area of study). This region inconsistency are happened in some land capability classes such as class II, III, IV and VI; and 3). Landcover is about 61779,31 Ha (9.05 % area of study).Keywords: evaluation, land capability, land cover, land suitability, regional land use plan